Transformasi ketatanegaraan Islam: Telaah historis terhadap ijtihad politik Umar bin Khattab - Rezki, Sri; M, Amril (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2025)
The leadership of Umar ibn al-Khattab marked a pivotal transformation in early Islamic governance, shifting Islam from a spiritual community into a structured political entity. This study examines the administrative reforms and statecraft innovations introduced by Umar, with a focus on his political ijtihad in shaping a functional and inclusive Islamic polity. Using a historical-critical approach and qualitative analysis of classical sources and modern scholarship, the paper explores Umar’s establishment of key institutions such as the Diwan system, separation of powers, judicial independence, public finance, and internal security. His reformist ijtihad, including the abolition of zakat for muallaf, suspension of hudud during famine, and institutionalization of public consultation, reflects a dynamic interpretation of Islamic governance responsive to socio-political realities. The study argues that Umar’s policies laid the foundational framework for Islamic constitutionalism and demonstrate the flexibility of Islamic law in adapting to administrative complexity. These reforms reveal not only Umar’s personal virtues of justice, consultation, and austerity but also a visionary political strategy that integrated religious principles with pragmatic state-building.